Homunculi of the Digital City - Minnie, Heinrich (Michaelis School of Fine Art, 2021)
Employing the media of video and installation, Homunculi of the digital city explores what it means to live in a digitally-mediated city. In my work, I personify both the city and city dwellers as cyborgian characters, by drawing on Donna Haraway's definition of the cyborg. I expand my personification further by employing the Homunculus from Johann Wolfgang von Goethe's Faust II (1950, originally published in 1832). I utilise Matthew Gandy, Ingrid Hoelzl and Rémi Marie's discussions around the broader city so to consider the material and immaterial elements that constitute it. The screens that populate contemporary cities embody both these elements: they are physical objects that perform invisible data, in the vein of Boris Groĭs' analogy of an image file being analogous to a piece of music that needs to be performed in order to be sensible. By drawing on these frameworks, I position the city as a high density of screens that are physically ubiquitous, often a prosthetic, and function as a gateway to the immaterial elements of the city.